2018
DOI: 10.5713/ajas.18.0349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optimal sodium stearoyl-2-lactylate supplementation on growth performance and blood and carcass characteristics in Hanwoo steers during the early fattening period

Abstract: ObjectiveThis study was conducted to evaluate the effect of different levels of total digestible nutrients (TDN) and sodium stearoyl-2-lactylate (SSL) supplementation on growth performance and blood and carcass characteristics in Hanwoo steers during the early fattening period.MethodsSixty Hanwoo steers (average body weight, 333±36.4 kg) were randomly allotted to 3 treatments, with twenty steers per treatment, and ten steers per pen with a size of 80 m2. Dietary treatments were as follows: CON, basal diet; tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Lactylates (LA) are esterified lactic acid and fatty acid compounds that have been approved by the Food and Drug Administration for use as emulsifiers in food production [ 13 ]. Recently, growing evidence of its benefits on animal husbandry has been described [ 14 ]. Several studies have demonstrated the beneficial effects of sodium stearoyl-2-lactylate (SSL) on growth performance and nutrient digestibility in young pigs and producing sows [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactylates (LA) are esterified lactic acid and fatty acid compounds that have been approved by the Food and Drug Administration for use as emulsifiers in food production [ 13 ]. Recently, growing evidence of its benefits on animal husbandry has been described [ 14 ]. Several studies have demonstrated the beneficial effects of sodium stearoyl-2-lactylate (SSL) on growth performance and nutrient digestibility in young pigs and producing sows [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 110 metabolites were identified and categorized into 12 chemical classes. The classes with the most metabolites were others (22), carboxylic acids (19), and carbohydrates (15) while with highest concentrations were carbohydrates (0.815 mM), organic acids (0.340 mM), and lipids (0.207 mM). In addition, 49 metabolites were quantified in the serum.…”
Section: Serum Metabolitesmentioning
confidence: 99%
“…-acetylglycine, (10) trimethylamine, (11) alanine, (12) 3-hydroxyphenylacetate, (13) cadaverine, (14) methylamine, (15) choline, (16) dimethylamine, (17) ethanol, (18) adenine, (19) anserine, (20) isoleucine, (21) phenylalanine, (22) uridine, (23) tyrosine, (24) galacarate, (25) threonine, (26) leucine, (27) methionine, (28) xanthine, (29) uracil, (30) ô-methylhistidine, (31) sucrose, (32) p-Cresol, (33) mannose, (34) O-acetylcholine, (35) creatine phosphate, (36) choline, (37) hypoxanthine, (38) gentisate, (39) thymidine, (40) malonate, (41) benzoate, (42) acetoacetate, (43) isopropanol, (44) 1,7-dimethylxanthine, (45)…”
Section: Serum Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations